Giant cell arteritis and scleritis: a rare association - Abrar-Ahmad Zulfiqar (Caspian Journal of Internal Medicine, 2022)
Background: Giant cell arteritis (GCA) is a vasculitis of the large and medium-sized arteries in the elderly whose ischemic complications adversely affect the eye. The irreversible loss of visual acuity is most often related to acute anterior ischemic optic neuropathy. Very few cases of scleritis have been described in the literature. Case Presentation: The patient presented an obvious case of giant cell arteritis, initially revealed by an ophthalmologic involvement in the form of posterior scleritis, an ear, nose, and throat (ENT) involvement with vestibular and neurological involvement with a type of peripheral neuropathy, all evolving in the context of a weight loss of 8 kg and a marked biological inflammatory syndrome. The patient presented several relapses of giant cell arteritis in the form of several episodes of anterior and posterior, right and left, and even bilateral, isolated scleritis without any other clinical or biological abnormalities, always in conjunction with a decrease in corticosteroid therapy. In the presence of corticosteroid dependence and resistance to methotrexate, tocilizumab was initiated. Conclusion: The therapeutic management of scleritis associated with giant cell arteritis is difficult. In the absence of a codified scheme, the treatment remains empirical, based on the experience of the various teams. In this context, biotherapies (anti-IL6 type, such as tocilizumab) are increasingly used.